2008
DOI: 10.1080/10803548.2008.11076750
|View full text |Cite
|
Sign up to set email alerts
|

Dry and Wet Heat Transfer Through Clothing Dependent on the Clothing Properties Under Cold Conditions

Abstract: The purpose of this study was to investigate the effect of moisture on the heat transfer through clothing in relation to the water vapour resistance, type of underwear, location of the moisture and climate. This forms part of the work performed for work package 2 of the European Union THERMPROTECT project. Thermal manikin results of dry and wet heat loss are presented from different laboratories for a range of 2-layer clothing with similar dry insulations but different water vapour permeabilities and absorptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…A considerable amount of moisture was trapped and accumulated in the liner during the experiment. Such moisture reduces both the thermal and evaporative resistance of the helmet ensemble and hence increases the total heat dissipation from the wearer (Lotens et al, 1995;Havenith et al, 2008;Richards et al, 2008). Furthermore, it is reported that absorbed water in the clothing layer increases both heat capacity and thermal conductivity.…”
Section: Evaporative Resistances and Permeability Index Of Helmet Ensmentioning
confidence: 94%
See 2 more Smart Citations
“…A considerable amount of moisture was trapped and accumulated in the liner during the experiment. Such moisture reduces both the thermal and evaporative resistance of the helmet ensemble and hence increases the total heat dissipation from the wearer (Lotens et al, 1995;Havenith et al, 2008;Richards et al, 2008). Furthermore, it is reported that absorbed water in the clothing layer increases both heat capacity and thermal conductivity.…”
Section: Evaporative Resistances and Permeability Index Of Helmet Ensmentioning
confidence: 94%
“…Moreover, the condensation would remain within the helmet ensembles. Published research has shown that condensation is responsible for the additional heat loss (Lawson et al, 2004;Richards et al, 2008). This is the speculated reason why evaporative resistance of the helmet ensembles can be lower than that in the naked head test (Chen et al, 2003).…”
Section: Evaporative Resistances and Permeability Index Of Helmet Ensmentioning
confidence: 95%
See 1 more Smart Citation
“…The various effects of moisture in protective clothing have been studied more extensively in recent years [79][80][81] . Moist layers (not fully saturated) may increase the heat loss by about 5%, while increased heat loss due to the "heat pipe" effect may reach up to 40%.…”
Section: Moisture In Footwearmentioning
confidence: 99%
“…So, WBGT is a great indicator of potential problems, however most probably only as an initial index. (Richards et al, 2008) confirmed the vital role of the clothing insulation in determining thermal comfort. A key concept marginally developed in current generic heat assessment methodologies such as the WBGT and the Fanger comfort model, is clothing permeability and moisture sorption and desorption under transient conditions which significantly increases the heat loss than simply summing the dry and evaporative heat loss.…”
Section: Literature Reviewmentioning
confidence: 61%